Analysis of Land Cover Changes in the Forest Area of Lindu Sub District Using Sentinel 2A Images - Misrah Misrah; Ida Arianingsih (Journal of Social Research, 2025)
Land cover change in forest areas are complex phenomena that have ecological, social, and economic impacts. Remote sensing is very useful for monitoring and mapping land cover changes because it can provide information about the earth's surface quickly, accurately, easily, and covers a wide area. Sentinel-2A imagery is a satellite remote sensing data with a high spatial resolution and has been widely used for land cover mapping. The study intends to analyze land cover changes in the forest area of Lindu District using Sentinel-2A imagery. The study was conducted in the forest region of Lindu Sub District, Central Sulawesi Province. The study found that the accuracy level of the classification output was 97.47% (Overall Accuracy) and 88.20% (Kappa Accuracy). The types of land cover produced consisted of forests, dryland agriculture, shrubs, grasslands, rice fields, swamp shrubs, and water bodies. Land cover that experienced changes were forests (decreased by 883.13 Ha), grasslands (decreased by 7.56 Ha), dryland agriculture (increased by 819.2 Ha), paddy field (decreased by 1.2 Ha), open land (increased by 36.31 Ha), and shrubs (increased by 28.23 Ha, swamp shrubs (increased by 9.51 Ha), water bodies (decreased by 1.36 Ha).